The community structure of soil fauna of roadside trees at three different elevations in Mauritius / Zaynab Jawaheer - Jawaheer, Zaynab (2014)
This study was carried out in Mauritius during summer from November 2012 to April 2013 and was designed to test the hypothesis that roadside tree diversity, elevation and bait type in pitfall traps affect soil fauna distribution and abundance The specific objectives of this study were to determine the species richness and diversity of roadside trees and to quantify the species richness, diversity, abundance and biomass of soil fauna of roadside trees in pitfall traps at different elevations. Soil fauna were collected utilizing pitfall traps made of plastic cups containing three different bait types (beef extract, beer and banana, and soap water) placed at three different elevations (Flic en Flac, 5m; Rose-Hill, 221m; and Mare aux Vacoas, 569m). Traps were placed among primary roadside tree species: Casuarina equisetifolia (Flic en Flac,), Dictyosperma album (Rose-Hill) and Pinus sylvestris (Mare aux Vacoas). A total of 18,114 individuals of soil fauna were sampled of which 10,142 individuals were sampled at Flic en Flac; 5293 individuals at Rose-Hill; and 2697 individuals at Mare aux Vacoas. The most abundant soil fauna among the three study sites was Carpophilus cheesmani (relative frequency=25.31%; relative abundance=46.54%). The heaviest soil fauna recorded was Achatina immaculata (mean biomass=1.2g). The Shannon Wiener Diversity varied significantly (p<0.05) between elevations (5m=1.84, 221m =1.21, 569m=2.54) while evenness was highest at 569m (0.92) followed by 5m (0.70) and lowest at 221m (0.42). The study sites with the highest soil fauna similarity were Mare aux Vacoas and Rose-Hill (0.71). Significant difference in soil fauna abundance and biomass was observed between elevations (<0.05), between months (<0.05) and between bait trap types (p<0.05). Significant correlations (p<0.05) between soil physiochemical parameters were recorded as well as their effect on soil fauna abundance. This study gives an initial view on the diversity, biomass and abundances of soil fauna from roadside trees of Mauritius. The results of this study support the concept that diversity of roadside trees and elevation have an impact on the community structure, abundance and biomass of soil fauna. This study can be useful in determining soil fauna and their plant host specificity as such data has implications for biological control as well as for collection of specific insects. This study also has implications for town planners with respect to planting roadside trees and their ensuing edaphic communities for managing insect pests. When comparing the three study sites, anthropogenic disturbances seem to have affected the soil fauna diversity, abundance and biomass. In this study, the observed effects have been highlighted and could be useful to beach authorities and municipal councils to avoid costly maintenance.